2006
DOI: 10.1007/s10856-006-9682-z
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic investigation on the osteogenesis at titanium implant/bone marrow interface under masticatory loading

Abstract: Electron microscopic investigation on osteogenetic process at the implant surface of threadless rod-type titanium implants with different surface roughness of Ra 0.4 +/- 0.01 microm, Sm 2.6 +/- 0.3 microm and Ra 2.0 +/- 0.12 microm, Sm 36 +/- 9.1 microm was performed at the early stage of 21 and 42 days post implantation into the jawbones of four beagles under the load bearing condition of functional mastication. The implant surfaces were covered with a blood clot and haematopoietic stem cells (HSC) including … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…This is probably owing to that Section 1 was nearest to the endosteum of the cortical bone, from which new bone tissue at the implant originated. An earlier work using electron microscopy supported that the osteoblasts of endosteum of cortical or trabecular bone could migrate to the titanium implant/bone marrow interface and undergo intramembranous bone formation [25].…”
Section: Discussionmentioning
confidence: 99%
“…This is probably owing to that Section 1 was nearest to the endosteum of the cortical bone, from which new bone tissue at the implant originated. An earlier work using electron microscopy supported that the osteoblasts of endosteum of cortical or trabecular bone could migrate to the titanium implant/bone marrow interface and undergo intramembranous bone formation [25].…”
Section: Discussionmentioning
confidence: 99%
“…An earlier work by Kawahara demonstrated that the osteoblasts of endosteum of cortical or trabecular bone could migrate to the titanium implant/bone marrow interface and undergo intramembranous bone formation. 23 The new bone in section 2 of Ti-15Mo-1Bi group, similar to that of section 1, may also have originated from the endosteum and remained constant in amount throughout 26 weeks. By contrast, in the Ti-6Al-4V group, the bone area of section 2 at 26 weeks becomes significantly reduced as compared with those at 6 and 12 weeks, indicating a retraction or absorption of the new bone tissue in the later period.…”
Section: Discussionmentioning
confidence: 85%
“…A purported assumption is that section 1 was nearest to the endosteum of the cortical bone, from which most of the new bone tissue surrounding the implant originated. An earlier work by Kawahara demonstrated that the osteoblasts of endosteum of cortical or trabecular bone could migrate to the titanium implant/bone marrow interface and undergo intramembranous bone formation 23. The new bone in section 2 of Ti‐15Mo‐1Bi group, similar to that of section 1, may also have originated from the endosteum and remained constant in amount throughout 26 weeks.…”
Section: Discussionmentioning
confidence: 89%